Optimizing Bus Rapid Transit for Equity in Madison, WI - Sanchez, Jacob; Gomez Parra, Orsen; Nelson, Alex (My University, 2018)
In Madison, WI the 2016 Metro Transit annual report cites overcapacity as the leading detriment to the system’s efficiency. This disproportionately affects low income, minority, and carless populations who rely on the transit system. The Madison Area Regional Transportation Plan 2050 has laid out a Bus Rapid Transit (BRT) system as a solution to this problem. Our goal is to implement a BRT plan emphasizing service to the origins and destinations of high density transit dependent populations. The final objective is an analysis of deviance between the MATPB plan and our own proposed route.
Includes Figures, Appendices, Maps and Bibliography.
Keywords: Madison, Wisconsin; Bus Rapid Transit; Equity; Metro Transit